2017
DOI: 10.1016/j.otsr.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological outcomes following radioscapholunate fusion

Abstract: RSL fusion is a palliative procedure that preserves some of the wrist's mobility. However, it is a difficult procedure that has a significant nonunion rate. Excision of the DPS may contribute to lowering the nonunion rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…6,14,25 In agreement with the literature, our results showed that DSE significantly reduced STT OA. 8,10,[13][14][15]26 We described three cases of STT OA despite DSE and suspected that the procedure was secondary to an incomplete excision.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…6,14,25 In agreement with the literature, our results showed that DSE significantly reduced STT OA. 8,10,[13][14][15]26 We described three cases of STT OA despite DSE and suspected that the procedure was secondary to an incomplete excision.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors reported this finding but not always provided the results on pain or strength. 10,14,15 The global OA rate after RSL fusion ranges from 0 to 100% in the literature, [8][9][10][11][12] but several series did not distinguish the involved joint: STT or midcarpal (e.g., scaphocapitate, lunocapitate, or triquetrohamate). Although the STT joint anatomically belongs to the midcarpal joint, we separated the two localizations of OA because their origins are different.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations